Counselling on The Negative Impact of Early Marriage - Dawous, Gilang Gumilang; Utami, Meryna Putri (Jurnal Al Maesarah, 2024)
Nationally, early age marriage is increasing significantly. This leads to a need for outreach to teenagers regarding the negative impacts of early marriage. Early age generally comes from promiscuity, customs and economic factors. Therefore, community service activities from academic circles are needed to provide understanding to teenagers who are starting to face puberty. Community service regarding counseling on the negative impacts of early marriage was held at MTs Al Ikhwan West Bandung in collaboration with STAI Darul Falah students asagent of changein the world of education. This research is Community Service which was carried out by impelementing Participatory Action Research (PAR). PAR is a research approach that involves active participation from the community being studied. Community service is carried out in 3 stages, the first is mapping potential and problems, the second is the implementation of early marriage socialization and the third is evaluating the implementation of early marriage socialization. This early marriage socialization program brings about social change in teenagers by creating new awareness towards better social transformation based on a strong foundation of religious character.